EVALUATION OF FACTORS THAT INFLUENCE THE MOTIVATION OF IT SPECIALISTS IN LATVIA - Gribanova, Svetlana; Abeltina, Anna; Ozols, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The present paper in dedicated to the research of factors that influence the motivation of Information Technology (further in the text IT) specialists in Latvia and the significance of these factors in overall motivation. The research contains a theoretical evaluation of approaches to measurement of motivation and presentation of the model of motivation metering. Being an internal individual condition, employees’ motivation is hard to be measured. However, attempts of measuring employees are regularly taken by research groups and individual scholars. As many factors such as gender, generation, profession and origin influence the motivation of the employee, we believe that there is no universal approach. The goal of the research is to evaluate the weight and significance of motivation factors and calculate the overall motivation of IT specialists in contemporary Latvia. The methodology used in the present research includes an evaluation of the theoretical models of measuring an employee’s motivation, suggestion of a mathematical model that is applicable to motivation measurement, conducting a survey of 78 IT specialists in Latvia and the approbation of the model.As the result, the factors that influenced IT specialists in Latvia were estimated, their influence on overall motivation was weighted, the motivation of IT specialists was measured and an analysis of the motivation of IT specialists that belonged to different genders and generations was performed.